2012
DOI: 10.2478/s11534-012-0006-2
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations in a parametrically excited Bose-Einstein condensate in combined harmonic and optical lattice trap

Abstract: Abstract:In this work, we study parametric excitations in an elongated cigar-shaped BEC in a combined harmonic trap and a time dependent optical lattice by using numerical techniques. We show that there exists a relative competition between the harmonic trap which tries to spatially localize the BEC and the time varying optical lattice which tries to delocalize the BEC. This competition gives rise to parametric excitations (oscillations of the BEC width). Regular oscillations disappear when one of the competin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The application of the modulation to both the HO and OL potentials makes the results more complex; nevertheless, in all cases, the VA predicts quasi-periodic dynamics, rather than dynamical chaos. The comparison to the direct simulations corroborates the validity of a majority of spectral peaks predicted by the VA. A quasi-one-dimensional BEC under the action of time-modulated potentials, such as harmonic-oscillator traps and optical lattices, may find various applications [56][57][58][59][60][61]116]. A comprehensive review of the respective technique of the spatiotemporal engineering in BEC is given in ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of the modulation to both the HO and OL potentials makes the results more complex; nevertheless, in all cases, the VA predicts quasi-periodic dynamics, rather than dynamical chaos. The comparison to the direct simulations corroborates the validity of a majority of spectral peaks predicted by the VA. A quasi-one-dimensional BEC under the action of time-modulated potentials, such as harmonic-oscillator traps and optical lattices, may find various applications [56][57][58][59][60][61]116]. A comprehensive review of the respective technique of the spatiotemporal engineering in BEC is given in ref.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found, in the experiment and the theory alike, that temporal modulation of the external trap or s-wave scattering length induces a variety of collective excitations in BEC [14,21,[43][44][45][46][47][48][49][50][51][52][53][54][55]. In particular, a quasi-one-dimensional BEC under the action of the HO potential combined with a temporally modulated OL is a relevant setting [56][57][58][59][60][61]. However, exact solutions of the GPE in the presence of a complex trap are not available even in lower dimensions, with the exception of models specially engineered so that to make them equivalent to the one-dimensional integrable NLSE [62].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also showed the possibility of suppression of chaos and its control through the intensity of the lattice potential. Recently, nonlinear resonance phenomenon has been studied in BEC, where the occurrence of resonances has been investigated through periodic modulation of the scattering length [28][29][30]. Unlike the methods opted in these studies, we take a different approach by introducing a lattice potential and show that it is possible to generate the nonlinear resonances in BEC, through controlled chirp management.…”
Section: Controlled Generation Of Nonlinear Resonances Through Sinuso...mentioning
confidence: 99%